ANALYSIS OF THE IMPLEMENTATION OF MICRO, SMALL, AND MEDIUM ENTITY FINANCIAL ACCOUNTING STANDARDS AND ITS IMPACTS ON THE FINANCIAL REPORT QUALITY OF SMALL AND MEDIUM-SIZED ENTERPRISES - Nikmatuniayah, Nikmatuniayah; Marliyati, Marliyati; Handayani, Jati; Anugrahwati, Lilis Mardiana (KEUNIS, 2023)
This study aims to identify the perception of entrepreneurs regarding the Importance of bookkeeping and financial report related to Amountount of credit received by MSMEs, as well as the prospects for implementing the Financial Standards for Micro, Small, and Medium Entities (SAK EMKM), and their impacts on the quality of MSMEs financial reporting. This study used primary data collection by using questionnaires. Questionnaires were distributed using the purposive sample method, with MSMEs spread across the Banyumanik and Tembalang sub-districts as samples. Were 40 questionnaires sent directly to the selected MSMEs as Amountount of evidence adequacy? An in-depth review was conducted on the MSMEs chosen to complete the data and discussion. The provisions of MSMEs are business actors who have been running for more than two years and have applied for bank credit financing. Respondent data can be processed in 32 respondents. The analytical technique used is the Hypothesis Testing Model by Rizki (2012). The analysis technique used is multiple regression analysis. The hypothesis test results showed that nine hypotheses were accepted, and five were rejected. It was found that educational background contradicted the Importance of bookkeeping and recording SAK EMKM financial statements.